Maladaptive Personality Traits and Psychopathological Symptoms in Individuals with the First Suicidal Attempt and with Chronic Suicidal Behavior - Kholmogorova A.B.; Subotich M.I.; Korkh M.P.; Rakhmanina A.A.; Bykova M.S. (Консультативная психология и психотерапия, 2020)
The paper compares the severity of maladaptive personality traits and psychopathological symptoms in patients with primary and repeated suicide attempts. The study involved patients of the somatopsychiatric department of the Sklifosovsky Research Institute of Emergency Care (N=61), who committed the first suicide attempt (n=31) or a repeated attempt (n=30). The results of the study did not reveal differences between the two groups in the severity of symptoms of social anxiety, depression and trait anxiety. However, indicators of such maladaptive personality traits as perfectionism and hypersensitive narcissism were significantly higher in the group of patients with a repeated suicide attempt. This group also manifested higher rates of the severity of borderline personality disorder traits and significant correlations between measures of psychopathology and maladaptive personality traits listed above. Conclusion: timely diagnostics of maladaptive traits and psychotherapy targeting socially prescribed perfectionism, hypersensitive narcissism, and borderline personality features after the first suicide attempt is necessary to prevent repeated ones.